Porous silica-doped calcium phosphate scaffolds prepared via in-situ foaming method - Šiška Virágová, Eliška; Novotná, Lenka; Chlup, Zdeněk; Šťastný, Přemysl; Šárfy, Pavlína; Cihlář, Jaroslav; Kučírek, Martin; Benák, Leoš; Streit, Libor; Kocanda, Jan; Sklenský, Jan; Filipovič, Milan; et al. (ELSEVIER SCI LTD, 2024)
The effect of silica (SiO2) addition (0 wt%-20 wt%) on the microstructural and mechanical properties, as well as the in vitro response of calcium phosphate scaffolds for potential application in bone tissue engineering (BTE) was investigated in this research. Scaffolds characterized by high porosity (77%-88 %) and interconnected spherical pores with a broad range of pore sizes (5-600 mu m) were fabricated using in-situ foaming method. Incorporated silica affected the phase transformation of hydroxyapatite (HA) to beta-tricalcium phosphate (beta-TCP) and led to the development of new crystalline silica-rich phases like silicocarnotite and wollastonite. The reinforcement of silica became apparent during the tests of mechanical properties. Scaffolds with 5 wt% of SiO2 exhibited compressive strength (1.13 MPa) higher than pure HA scaffolds (0.93 MPa). Bone bonding potential of the materials was tested in simulated body fluid (SBF), demonstrating this potential in silica-doped samples. Additionally, degradation experiments showed gradual material degradation, making it suitable for BTE applications. Furthermore, cell culture studies using human mesenchymal stromal cells (MSC) confirmed the scaffold's non- toxicity and provided insights into how the silica content influences cell viability, morphology, and osteogenic potential. The findings of this study offer valuable insights into the design and development of advanced scaffolds with tailored properties for effective BTE applications.

The effect of silica (SiO2) addition (0 wt%-20 wt%) on the microstructural and mechanical properties, as well as the in vitro response of calcium phosphate scaffolds for potential application in bone tissue engineering (BTE) was investigated in this research. Scaffolds characterized by high porosity (77%-88 %) and interconnected spherical pores with a broad range of pore sizes (5-600 mu m) were fabricated using in-situ foaming method. Incorporated silica affected the phase transformation of hydroxyapatite (HA) to beta-tricalcium phosphate (beta-TCP) and led to the development of new crystalline silica-rich phases like silicocarnotite and wollastonite. The reinforcement of silica became apparent during the tests of mechanical properties. Scaffolds with 5 wt% of SiO2 exhibited compressive strength (1.13 MPa) higher than pure HA scaffolds (0.93 MPa). Bone bonding potential of the materials was tested in simulated body fluid (SBF), demonstrating this potential in silica-doped samples. Additionally, degradation experiments showed gradual material degradation, making it suitable for BTE applications. Furthermore, cell culture studies using human mesenchymal stromal cells (MSC) confirmed the scaffold's non- toxicity and provided insights into how the silica content influences cell viability, morphology, and osteogenic potential. The findings of this study offer valuable insights into the design and development of advanced scaffolds with tailored properties for effective BTE applications.
Porous silica-doped calcium phosphate scaffolds prepared via in-situ foaming method
Keywords: Calcium phosphates; Silica; In-situ foaming; Mechanical strength; In vitro response; Calcium phosphates; Silica; In-situ foaming; Mechanical strength; In vitro response